Stroke Mortality, Clinical Presentation and Day of Arrival: The Atherosclerosis Risk in Communities (ARIC) Study - Emily C. O'Brien; Kathryn M. Rose; Eyal Shahar; Wayne D. Rosamond (Stroke Research and Treatment)
Background. Recent studies report that acute stroke patients who present to the hospital on weekends have higher rates of 28-day mortality than similar patients who arrive during the week. However, how this association is related to clinical presentation and stroke type has not been systematically investigated. Methods and Results. We examined the association between day of arrival and 28-day mortality in 929 validated stroke events in the ARIC cohort from 1987–2004. Weekend arrival was defined as any arrival time from midnight Friday until midnight Sunday. Mortality was defined as all-cause fatal events from the day of arrival through the 28th day of followup. The presence or absence of thirteen stroke signs and symptoms were obtained through medical record review for each event. Binomial logistic regression was used to estimate odds ratios and 95% confidence intervals (OR; 95% CI) for the association between weekend arrival and 28-day mortality for all stroke events and for stroke subtypes. The overall risk of 28-day mortality was 9.6% for weekday strokes and 10.1% for weekend strokes. In models controlling for patient demographics, clinical risk factors, and event year, weekend arrival was not associated with 28-day mortality (0.87; 0.51, 1.50). When stratified by stroke type, weekend arrival was not associated with increased odds of mortality for ischemic (1.17, 0.62, 2.23) or hemorrhagic (0.37; 0.11, 1.26) stroke patients. Conclusions. Presence or absence of thirteen signs and symptoms was similar for weekday patients and weekend patients when stratified by stroke type. Weekend arrival was not associated with 28-day all-cause mortality or differences in symptom presentation for strokes in this cohort.